Associations between low‐carbohydrate and low‐fat diets and hepatic steatosis. Issue 11 (4th September 2022) - Li, Xiude; Li, Meiling; Xu, Linsheng; Zeng, Xueke; Zhang, Tengfei; Yang, Hu; Li, Haowei; Zhou, Zhihao; Wang, Yu; Zhang, Chenghao; Zhu, Yu; Huang, Yong; et al.
Abstract: Objective: This study assessed the cross‐sectional associations of low‐carbohydrate diets (LCDs) and low‐fat diets (LFDs) with hepatic steatosis in the National Health and Nutrition Examination Survey. Methods: Diet was measured using the 24‐hour recalls. Hepatic steatosis was defined by vibration‐controlled transient elastography. The odds ratios (OR) and 95% confidence intervals (CI) were estimated using logistic regression. Substitution analysis was performed using the leave‐one‐out model. Results: Participants with higher adherence scores (comparing extreme tertiles) for an overall (OR = 0.76, 95% CI: 0.61‐0.96, p trend  = 0.049) or a healthful LCD (OR = 0.61, 95% CI: 0.43‐0.87, p trend  < 0.001) exhibited lower odds of steatosis. Replacing 5% of the energy from carbohydrates with total fat and protein (OR = 0.91, 95% CI: 0.83‐0.99) or unsaturated fat and plant protein (OR = 0.89, 95% CI: 0.84‐0.94) was associated with lower steatosis prevalence. High overall (OR = 1.65, 95% CI: 1.13‐2.40, p trend  = 0.006) or unhealthful (OR = 1.41, 95% CI: 1.10‐1.80, p trend  < 0.001) LFD scores were associated with increased likelihood of steatosis. Conclusions: These findings suggest that the associations between LCDs and LFDs and steatosis may depend on the quality and food sources of the macronutrients.